SOAR Analysis for Audit Dilemmas in Non-Budgeted Cash Grants: A Case Study of East Tanjung Jabung Regency - Abdurahman, Abdurahman; Irfan Mahfuddin (Asia Pacific Fraud Journal, 2025)
This study explores the potential for fraud in transactions not directly tied to local government financial mechanisms, with a focus on the mechanism of granting in-kind donations from third parties to local governments. While these donations are formally given as goods, the process involves local governments managing third-party funds to procure the goods for donation. This research aims to address the auditors’ dilemma in rationalizing cash donation transactions handled outside the state financial system. This research adopts a qualitative methodology through a case study focused on Tanjung Jabung Timur Regency, drawing on data from the 2023 Audit Report of the Local Government Financial Statements. Using the SOAR framework for analysis, the study finds that cash grants managed outside the regional budget mechanism are still subject to state financial audits. This contributes to addressing the perception among local governments that such funds are excluded from state finances and provides a foundational step for developing audit procedures.